Central Nervous System Diseases due to Opportunistic and Coinfections - Ho, Emily L.; Marra, Christina M. (Seminars in Neurology, 2014)
With the widespread use of combination antiretroviral therapy (cART), the incidence of central nervous system (CNS) opportunistic infections and coinfections has significantly decreased. This review focuses on the clinical presentation, diagnostic laboratory and radiologic findings, as well as the treatment of neurosyphilis, progressive multifocal leukoencephalopathy, primary CNS lymphoma, and toxoplasmosis, which are CNS opportunistic infections and coinfections that are most relevant to clinicians in North America.
Keywords: human immunodeficiency virus; central nervous system; opportunistic infection; coinfection; lymphoma